Establishment of a stable, effective and universal genetic transformation technique in the diverse species of Brassica oleracea - Sheng, Xiaoguang; Yu, Huifang; Wang, Jiansheng; Shen, Yusen; Gu, Honghui (Frontiers in Plant Science, 2022)
Brassica oleracea is an economically important species including seven cultivated variants. Agrobacterium-mediated transformation of B. oleracea crops, mainly via hypocotyl and cotyledon, has been achieved in the past. However, previously established transformation methods showed low transformation efficiency, serious genotype limitation and took a prolonged period for transformants acquisition, greatly restricting its application in functional genomic studies and crop improvement. In this study, we have compared the shoot regeneration efficiency and genetic transformation with hypocotyl, cotyledon petiole and curd peduncle explants from twelve genotypes of cauliflower and broccoli. Finally, an Agrobacterium-mediated transformation method using curd peduncle as explant was established, which is rapid, efficient, and amenable to high-throughput transformation and genome editing. The average genetic transformation efficiency of this method is stable up to 11.87%, and was successfully implemented in twelve different genotypes of cauliflower and broccoli and also other B. oleracea crops with genotype-independence. Peduncle explants were found to contain abundant cambial cells with strong ability of cell division and shoot regeneration, which might be the reason for this method to achieve stable and high genetic transformation efficiency with almost no genotype dependence.